Modulation Transfer Function for Optimum Performance in Vision Systems: The modulation transfer function can be used from system to sensor for the measurement of lenses, sensors, and the entire vision system. Issue 1 (28th January 2019) - Simon, Stephanie
Abstract: The quality of a vision system is influenced by many factors; primarily by the resolution of the lens and the sensor. The modulation transfer function (MTF) is a well‐established method for determining and comparing the resolution of lenses. However, for the performance assessment of the overall system, the resolution of the sensor must be taken into additional consideration. How can the sensor be incorporated into this model? This article explains the fundamentals of the optical transfer function and the resulting MTF. In addition, the other important factors that influence sensors and lenses are explained in detail, to provide the optimum performance of a vision system.